Large unconventional anomalous Hall effect far above room temperature in epitaxial Fe3Ga4 films - Jing Meng; Huali Yang; Yu Shen; Kun Zheng; Hongru Wang; Yuhao Wang; Keqi Xia; Bocheng Yu; Xiaoyan Zhu; Baiqing Lv; Yaobo Huang; Jie Ma; et al. (npj Quantum Materials)
Abstract Noncoplanar spin textures usually exhibit a finite scalar spin chirality (SSC) that can generate effective magnetic fields and lead to additional contributions to the Hall effect, namely topological or unconventional anomalous Hall effect (UAHE). Unlike topological spin textures (e.g., magnetic skyrmions), materials that exhibit fluctuation-driven SSC and UAHE are rare. So far, their realization has been limited to either low temperatures or high magnetic fields, both of which are unfavorable for practical applications. Identifying new materials that exhibit UAHE in a low magnetic field at room temperature is therefore essential. Here, we report the discovery of a large UAHE far above room temperature in epitaxial Fe3Ga4 films, where the fluctuation-driven SSC stems from the field-induced transverse-conical-spiral phase. Considering their epitaxial nature and the large UAHE stabilized at room temperature in a low magnetic field, Fe3Ga4 films represent an exciting, albeit rare, example of a promising material for spintronic devices.